Automatic Fan Design Based on Microcontroller with Combination of DHT11 Sensor and Motion Sensor - Rahayu, Intan Dwi; Basri, Mhd (Ilmu Bersama Center, 2024)
The development of a more sophisticated fan is a necessity. One way to improve fan performance is to add temperature and humidity sensors, so that the fan can rotate automatically according to the desired temperature and humidity. By using the Arduino Nano microcontroller, DHT11 sensor and Motion PIR sensor, the fan can be controlled automatically and can rotate at a speed set according to the temperature and humidity measured by the DHT11 sensor, and can detect whether there are people inside by using the Motion PIR sensor. That way, the fan can work more effectively and efficiently in maintaining coolness and air quality in the room. In addition, the use of microcontrollers, DHT11 sensors, and PIR motion sensors also makes it easier for users to manage fans and maintain temperature and humidity in the room more easily. Therefore, by utilizing the DHT11 sensor and PIR sensor and controlled by the Arduino Nano microcontroller. The test results obtained are the fan will turn on in a temperature condition of 30oc or there are people in the room and the fan will turn off if it does not meet these conditions. With a system like this it will extend the life of the fan and make it practical in turning on and off the fan.